Characterization of monomeric and soluble aggregated Aβ in Down's syndrome and Alzheimer's disease brains: Human neuropathology/amyloid. (7th December 2020) - Gkanatsiou, Eleni; Sahlin, Charlotte; Portelius, Erik; Johannesson, Malin; Söderberg, Linda; Fälting, Johanna; Basun, Hans; Möller, Christer; Odergren, Tomas; Zetterberg, Henrik; Blennow, Kaj; Lannfelt, Lars; et al.
Abstract: Background: Alzheimer's disease (AD) is the most common form of dementia and is characterized by the two hallmarks, amyloid plaques and neurofibrillary tangles in the brain. The plaques consist of aggregated beta amyloid (Aβ) peptides, formed by proteolytic cleavages of amyloid precursor protein (APP). Down's syndrome (DS) is a genetic disease with an extra copy of chromosome 21, harbouring the APP gene. DS individuals are at increased risk to develop amyloid pathology. Most DS have substantial amyloid pathology at their 40s, with clinical signs of deterioration before the age of 60. Our aim was to compare the Aβ peptide pattern in DS and AD brains, to better understand the difference between them. Methods: Immunoprecipitation (IP) in combination with mass spectrometry was used to identify both soluble and insoluble Aβ peptides, as well as to characterise the composition of Aβ oligomers/protofibrils. Two different antibody combinations were used; 6E10+4G8 to identify total Aβ peptide contents and the Aβ protofibril selective antibody mAb158 to identify the Aβ peptides present in oligomers/protofibrils. Before IP, cortical tissue from patients with DS (with amyloid pathology), sporadic AD and controls were homogenized and fractionated into TBS (TBS soluble) and formic acid (insoluble) fractions. Results: From IP with 6E10+4G8 several truncated Aβ peptides were identified in all groups, including: 1‐X, 2‐X, 3‐X, 4‐X, 5‐X, 11‐X and –X to 15 as well as post‐translationally modified peptides with oxidation and pyroglutamation. Similarities were observed when comparing the Aβ peptide processing in AD and DS, with the exception of –X to 15 Aβ peptides for which the pattern is different. By using mAb158, Aβ1‐40, Aβ1‐42 and Aβ4‐42 were identified. Higher relative AβX‐42 signals were obtained compared to samples IP'd with 6E10+4G8, indicating that the protofibrils/oligomers were enriched with peptides ending at aa42. Conclusion: All Aβ peptides found in AD are also present in DS (with amyloid pathology) indicating a generally similar pathway of Aβ peptide production, apart from –X to 15. Likewise, the Aβ peptides forming protofibrils/oligomers in both AD and DS were similar, implying the possibility to exploit the potential utility of a treatment with clinical benefit in sporadic AD for subjects with DS.